Kinetic Monte Carlo Study of the Sensitivity of OLED Efficiency and Lifetime to Materials Parameters. (4th November 2014) - Coehoorn, Reinder; van Eersel, Harm; Bobbert, Peter; Janssen, René
Abstract : The performance of organic light‐emitting diodes (OLEDs) is determined by a complex interplay of the optoelectronic processes in the active layer stack. In order to enable simulation‐assisted layer stack development, a three‐dimensional kinetic Monte Carlo OLED simulation method which includes the charge transport and all excitonic processes is developed. In this paper, the results are presented of simulations including degradation processes in idealized but realizable phosphorescent OLEDs. Degradation is treated as a result of the conversion of emitter molecules to non‐emissive sites upon a triplet‐polaron quenching (TPQ) process. Under the assumptions made, TPQ provides the dominant contribution to the roll‐off. There is therefore a strong relationship between the roll‐off and the lifetime. This is quantified using a "uniform density model", within which the charge carrier and exciton densities are assumed to be uniform across the emissive layer. The simulations give rise to design rules regarding the energy levels, and are used to study the sensitivity of the roll‐off and lifetime to various other materials parameters, including the mobility, the phosphorescent dye concentration, the triplet exciton emissive lifetime and binding energy, and the type of TPQ process. Abstract : Kinetic Monte Carlo simulations are used to mechanistically analyze the influence of organic semiconductor materials properties on the luminance decay due to degradation processes in phosphorescent organic light emitting diodes. A relationship is established between the lifetime and the efficiency roll‐off with increasing current density, assuming triplet‐polaron quenching processes as the root‐cause of the degradation, and design rules regarding the energy levels are developed.